Weathering the economic impact of COVID-19: challenges faced by microentrepreneurs and their coping strategies during Movement Control Order MCO in Malaysia - Megat Tajudin, Putri Noorafedah; Abd Rahim, Nur Aira; Idris, Khairuddin; Arshad, Mohd Mursyid (Universiti Putra Malaysia, 2021)
The COVID-19 pandemic is a global crisis that has caused a punishing economic impact on businesses, particularly due to many countries adopting measures such as the Movement Control Order (MCO) to curb the spread of the COVID-19 disease. The impact hits the most on microentrepreneurs since they are not able to operate their businesses, of which the margins of profit and resources are relatively small. The purpose of this research was to explore the challenges faced by microentrepreneurs during MCO and their coping strategies used to overcome these challenges. This study utilized the qualitative case study approach and collected interview data among the identified microentrepreneurs that met the criterion sampling. The findings uncover that these microentrepreneurs typically faced challenges related to restricted cash flows, lack of customers and supplies shortage issues which impacted their income and business operations during MCO. These challenges were addressed using coping strategies, namely having the ability to control stress, developing a strong spiritual relationship with God, applying problem solving thinking skills, utilizing social capital (offline and online), and optimizing digital marketing. It is recommended that government agencies, NGOs, and social movement bodies contribute to microentrepreneurs by organising and engaging in digital empowerment programs to enable rural entrepreneurs to leverage on their access to digital commerce, internet marketing and alike.